International Scientist Mobility and the Locus of Technology Transfer - Jakob Edler; Heide Fier; Christoph Grimpe (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
University technology transfer has attracted considerable attention in the literature with a focus on the institutions, the agents involved in technology commercialisation or the differentiation between formal and informal technology transfer mechanisms. There has, however, been little systematic research on how the mobility of university scientists influences their propensity to engage in technology transfer activities and, particularly, on how mobility influences the locus of such activities. This paper therefore analyses the link between university scientists' technology transfer activities and their international mobility patterns. We characterise scientist mobility along the two dimensions 'frequency' and 'intensity' resulting in an individual mobility pattern. We argue that the mobility pattern as well as the scientist's personal characteristics affects the likelihood whether a transfer of technology occurs to a firm in the scientist's home and/or host country. Based on a sample of more than 500 German university scientists, our results indicate that a substantial share of scientists engages in technology transfer both to the home as well as to the host country. There are, however, considerable differences regarding the factors influencing the locus of technology transfer.
Keywords: O33; J61; 330; scientist mobility; university technology transfer; internationalisation; Wissenschaftler; Internationale Arbeitsmobilität; Wissenstransfer; Technologietransfer; Deutschland